Effect of Potassium Nitrate (KNO3) Concentration and Duration of Osmopriming on the Quality of Deteriorated Green Amaranth (Amaranthus spp.) Seeds - Hatika Rahmawan; Adhitya Vishnu; Mertya Anugrah (Akta Agrosia, 2026)
Amaranth seeds cultivated for agricultural purposes may experience a decline in vigor and viability beyond their expiration date, resulting in reduced or failed germination. Osmopriming, a seed priming technique, germination capacity, and seedling vigor by regulating partial hydration while preventing premature radicle protrusion. The objective of this research to certain effective concentration and soaking duration of KNO3. The experiment used six-year expired green amaranth seeds and a two-factor factorial Completely Randomized Design (CRD). The first factor was KNO3 concentration at 0% (water), 1%, 2%, 3%, 4%, and 5%, and the second factor was soaking duration at 1 and 10 minutes. The observations encompassed germination percentage, vigor index, and radicle emergence, among other parameters. KNO₃ osmopriming effectively restores the viability and vigor of deteriorated green amaranth seeds. The most effective treatment is 2% concentration of KNO3 and 10 minute soaking time duration for germination capacity and vigor index. Keywords: amaranthaceae, germination, imbibition, priming, radicle emergence